Tinjauan Awal Mengenai Persepsi Masyarakat Islam Terhadap Konsep Islam Hadhari: Kajian Di Lembah Klang - Md. Yunus Abd Aziz; Abd Hamid Abd Murad; Arif Fahmi Md Yusof; Nik Salida Suhaila Nik Saleh (Universiti Sains Islam Malaysia, 2024)
The concept of lslam Hadhari is introduced by Malaysian Government and announced by YAB Perdana Menteri Malaysia, Dato' Seri Abdullah Haji Ahmad Badawi. Basically, this concept is acquainted to give a clear picture of lslam to the Muslim society as a whole and also others in Malaysia. Currently, there are many interpretations of lslam Hadhari given to the society by individual or certain group of people. Therefore, this research is an exploratory and preliminary research to understand the perception of society towards lslam Hadhari introduced by the Government. It is aiming at ensuring the understanding, attitudes and perception of the Muslim society about lslam Hadhari including their source of information. The targeted respondent of this research are Muslim society in Klang Valley by considering their various background of education and location. Research questions that have been issued are gathered and analyzed. Finally, the result or finding of that particular analysis is stated and attached in this report.